2019
DOI: 10.1021/acs.jmedchem.8b01943
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Epoxyketone-Based Proteasome Inhibitors as a Strategy To Overcome Cancer Resistance to Carfilzomib and Bortezomib

Abstract: Over the past 15 years, proteasome inhibitors (PIs), namely bortezomib, carfilzomib (Cfz) and ixazomib, have significantly improved the overall survival and quality-of-life for multiple myeloma (MM) patients. However, a significant portion of MM patients do not respond to PI therapies. Drug resistance is present either de novo or acquired after prolonged therapy through mechanisms that remain poorly defined. The lack of a clear understanding of clinical PI resistance has hampered the development of next-genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…Many previous studies have demonstrated that targeting the primed site can be an effective strategy for developing potent or selective inhibitors of proteases of viruses such as human immunodeficiency virus and hepatitis C virus [ [25] , [26] , [27] ]. Recently, several groups have reported α-keto phenylamide and epoxyketone based proteasome inhibitors targeting the primed site to increase potency or overcome resistance [ 21 , 45 ]. It was shown that the targeting of the primed site by 3-phenoxy phenyl could increase β5 inhibition of a compound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies have demonstrated that targeting the primed site can be an effective strategy for developing potent or selective inhibitors of proteases of viruses such as human immunodeficiency virus and hepatitis C virus [ [25] , [26] , [27] ]. Recently, several groups have reported α-keto phenylamide and epoxyketone based proteasome inhibitors targeting the primed site to increase potency or overcome resistance [ 21 , 45 ]. It was shown that the targeting of the primed site by 3-phenoxy phenyl could increase β5 inhibition of a compound.…”
Section: Discussionmentioning
confidence: 99%
“…β-Lactone homobelactosin C primarily binds to the primed site exhibiting high potency to β5 subunit [ 19 , 20 ]. A recent study has shown that epoxyketone-based compounds targeting P1’ site have the efficacy against cell lines of de novo or acquired resistance to carfilzomib [ 21 ]. Thus, discovery of new compounds capable of binding the primed site remains an area to be explored further.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al recently reported a novel epoxyketone 77, which not only inhibits the ChT-L activity of proteasome from RPMI8226 cell lysates (IC 50 : 2.1 AE 0.9 nM), but also inhibits proteasome activity (ChT-L) nearly three-fold more potently in RPMI8226-Cfz resistant cells than carfilzomib itself (IC 50 : 106.2 AE 28.9 nM). 193 Other recent advances of the epoxyketone moeity include the design of selective inhibitors for the b1i, 194,195 b2i, 196,197 and b5i subunits. 198 The epoxyketone-containing natural products carmaphycin A and B were isolated from marine cyanobacterium Symploca sp.…”
Section: Reviewmentioning
confidence: 99%
“…However, cancer resistance, either de novo or acquired, remains a major obstacle in expanding the clinical utility of PI drugs. Kyung Bo Kim and his co-workers have developed a series of peptide epoxyketones bearing a P1′-targeting moiety, of which the most potent Cfz−OH (IC 50 = 29.4 nM) showed an IC 50 value against H23 cells similar to that of carfilzomib (Cfz, IC 50 = 18.3 nM) [12]. Moreover, Cfz−OH demonstrated improved potency by ~10-fold and 3-fold relative to Cfz in models of de novo and acquired Cfz resistance, respectively.…”
Section: Novel Epoxyketone-based Proteasome Inhibitors With Enhancmentioning
confidence: 99%